P05.06 Phase 2 study to evaluate the safety, pharmacokinetics and clinical activity of PI3K/mTOR inhibitor GDC-0084 given to glioblastoma (GBM) patients with unmethylated O6-methylguanine-methyltransferase (MGMT) promoter status. (6th September 2019) - Wen, P Y; de Groot, J; Battiste, J D; Goldlust, S A; Garner, J; Simpson, J; Olivero, A; Cloughesy, T
Abstract: BACKGROUND: GDC-0084 is a potent, oral, selective small molecule inhibitor of class I phosphoinositide 3-kinase and mammalian target of rapamycin (PI3K/mTOR). The PI3K pathway is activated in ≥ 70% of tumors, making it a compelling target for the treatment of GBM. GDC-0084 crosses the blood-brain barrier and achieves a brain / plasma ratio of approximately 1.0. GDC-0084 was given as once daily oral dosing in a phase 1 study (Wen et al, J Clin Oncol 34, 2016(15) suppl.2012) in 47 patients with recurrent high-grade gliomas. The adverse events were generally consistent with the established PI3K/mTOR inhibitor class-effects. The MTD identified was 45 mg once daily. MATERIAL AND METHODS: This study has a 2-part design consisting of an open-label, multicenter dose-escalation study with expansion to assess the safety, tolerability, RP2D, PK, and clinical activity of GDC-0084 at QD dosing in patients with newly-diagnosed GBM with unmethylated MGMT promotor status. In the escalation phase the first cohort is completed without DLT. At the identified MTD, 20 subjects will be recruited in an expansion cohort and patients will be randomized to take GDC-0084 in fed and fasted states. Subjects in the expansion cohort will also have serial fluorodeoxyglucose-positron emission tomography (FDG-PET) imaging.